The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1038/sj.bmt.1701585
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell component therapy: supplementation of unmanipulated marrow with CD34 enriched peripheral blood stem cells

Abstract: Summary:Eleven patients with hematologic malignancies and two with aplastic anemia were treated using unmanipulated marrow and immunoselected CD34 ؉ blood cells. Donors began G-CSF (10 g/kg) injections 1 day after undergoing bone marrow harvest. Blood stem cells were collected on day 5 of G-CSF. Peripheral blood lymphocytes were depleted via CD34-positive selection. If, after marrow and blood harvest, less than 2.0 ؋ 10 6 CD34 cells/kg were mobilized, leukapheresis was repeated on day 6. Median time to an abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…In terms of engraftment, our results appear superior to other studies, taking the multiple transfusions and long disease duration into consideration. Engraftment of neutrophils and platelets occurred on days 12 and 17, respectively, which are comparable with the results of high-dose stem cell transplants, previously reported [13,14].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In terms of engraftment, our results appear superior to other studies, taking the multiple transfusions and long disease duration into consideration. Engraftment of neutrophils and platelets occurred on days 12 and 17, respectively, which are comparable with the results of high-dose stem cell transplants, previously reported [13,14].…”
Section: Discussionsupporting
confidence: 76%
“…Feasibility studies into the use of the combination of unmanipulated marrow and T-cell depleted PBSC as the stem cell source for allogeneic BMT have shown rapid engraftment without increasing the risk of GVHD [13,14]. No similar data are yet available for SAA.…”
Section: Introductionmentioning
confidence: 99%
“…4 A new trial assessing the addition of fludarabine (FLU) to a reduced dose of CY with ATG has shown good engraftment in heavily sensitized patients, whereas a high incidence of acute and chronic GVHD was also noted in that study. 13 On the basis of feasibility studies conducted by other groups, 15,16 we have applied a method that uses the combination of unmanipulated BM and T-cell-depleted PBSCs as a source of stem cells for high-risk patients with SAA to ensure engraftment. Our pilot studies showed a reduction in graft rejection and a faster engraftment speed, without any apparent increase in GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…2) [4]. This approach would contribute to the rapid engraftment kinetics of peripheral blood stem cells, allowing for an increase in stem cell dose without an increased risk of chronic GVHD.…”
Section: Mavroudis Et Almentioning
confidence: 99%
“…In allogeneic transplantations, CD34 + dose correlates with early and late hematopoiesis and hospital charges. It is possible but unproven that CD34 + dose may impact on survival, and possibly GVHD [4,5].…”
Section: Cell Markersmentioning
confidence: 99%